Analysis of EEG Lemple–Ziv complexity and correlative aspects before and after treatment of anti-syphilis therapy for neurosyphilis. (4th March 2019) - Jiang, MJ; Zhang, HJ; Li, WR; Wu, WQ; Huang, YM; Xu, DM; Qi, YY; Qin, KY; Zhang, L; Zhang, JL
ABSTRACT: Objective To investigate the diagnostic value of electroencephalogram (EEG) complexity in patients with neurosyphilis by comparing the changes of electroencephalogram Lempel-Ziv complexity (EEG-LZC) before and after anti-syphilis treatment. Methods The EEG complexity of neurosyphilis patients diagnosed in our hospital from July in 2015 to June in 2017 was analyzed and compared with other diagnostic results such as serology examination and cerebrospinal fluid examination. Results A total of 27 patients were diagnosed, including 19 males and 8 females, of which 6 were mesenchymal(cerebrospinal membrane and meningeal vascular), 16 were parenchymal(paralytic dementia, spinal cord tuberculosis and optic neuropathy), and 5 were asymptomatic. After intensive anti-syphilis therapy, the LZC increased significantly in all patients while the trend and degree of change were consistent with other diagnostic results. Conclusion The LZC can be used as one of the diagnostic indexes meanwhile the trend and degree of its change can be used as the reference index of curative effect to neurosyphilis.